2015
DOI: 10.1144/jgs2015-069
|View full text |Cite
|
Sign up to set email alerts
|

Frontier exploration and the North Atlantic Igneous Province: new insights from a 2.6 km offshore volcanic sequence in the NE Faroe–Shetland Basin

Abstract: The Lagavulin exploration well 217/15-1Z penetrated a ~2.6 km thick volcanic sequence dominated by extrusive basaltic rocks spanning the Palaeocene-Eocene boundary in the NE Faroe-Shetland Basin (FSB). The well comprises one of the thickest drilled sequences through the North Atlantic Igneous Province. Integrated analysis of drill cuttings and wireline-log data reveals key volcanic lithofacies: i) tabular lava flows; ii) compound lava flows; iii) hyaloclastite; and iv) volcaniclastic rocks. The volcanic facies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 74 publications
(119 reference statements)
4
68
0
Order By: Relevance
“…However, in many other cases, the uniformly low primary gamma response of thick lava packages (e.g. Planke, 1994;Nelson et al, 2009;Millett et al, 2015) may limit the viability of geophysical means for borehole correlation, outside of facies characterization (e.g. Nelson et al, 2009) which, as demonstrated by this study, does not form a robust criteria for correlation by itself.…”
Section: Accepted M Manuscriptmentioning
confidence: 70%
See 2 more Smart Citations
“…However, in many other cases, the uniformly low primary gamma response of thick lava packages (e.g. Planke, 1994;Nelson et al, 2009;Millett et al, 2015) may limit the viability of geophysical means for borehole correlation, outside of facies characterization (e.g. Nelson et al, 2009) which, as demonstrated by this study, does not form a robust criteria for correlation by itself.…”
Section: Accepted M Manuscriptmentioning
confidence: 70%
“…(Jerram, 2015;Millett et al, 2015) along with the potential for CO 2 sequestration (Zakharova et al, 2012) and natural gas storage (Reidel et al, 2002). Understanding the potential but also the limitations of geochemical correlation within LIP sequences is therefore important for the effective exploration and development of resources associated with LIPs.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Jerram et al, 2009;Planke et al, 2015;Schofield et al, 2016), as well as an understanding of the petrophysics of the volcanic rocks from borehole core and wireline data (e.g. Planke et al, 1999;Japsen et al, 2004;Nelson et al, 2009;Watton et al, 2014;Millett et al, 2015). With these advances in our understanding of volcanic margins, targeted 3D seismic data over key volcanic areas will provide valuable insights into how these margins develop through time and are preserved in the offshore rock record.…”
Section: Introductionmentioning
confidence: 99%
“…Often, the interpretation of logging data from volcanic materials (e.g. Millett et al, 2016) is non-trivial due to the variable quality of density logs and variations in the relationship between density and porosity with depth, alteration, or the intersection of distinct facies (Li et al, 2009), as well as gaps in the stratigraphic record due to incomplete core recovery. An example of a study with an excellent degree of core recovery -99.7 % -is reported by Jónsson and Stefánsson (1982): these authors calibrate porosity and density data obtained by the Iceland Research Drilling Project from a borehole cored continuously to a depth of 1919 m near Reyðarfjörður in Iceland.…”
Section: Introductionmentioning
confidence: 99%